2021
DOI: 10.1155/2021/7933453
|View full text |Cite
|
Sign up to set email alerts
|

IL-38 and IL-36 Target Autophagy for Regulating Synoviocyte Proliferation, Migration, and Invasion in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease leading to severe joint damage and disability. Fibroblast-like synoviocytes (FLSs) mostly contribute to the joint inflammation and destruction in RA through distinct mechanisms. However, little is known about newly discovered interleukin- (IL-) 36 and IL-38 involving in the pathology of RA. Here, we assessed the effect of IL-36 and IL-38 on RA-FLS function using IL-36 and IL-38 overexpression plasmids. We found that IL-36 inhibited synoviocytes proliferation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…不同IL-36亚型在类风湿关节炎中的作用目前尚存在争议。在胶原性关节炎和K/BxN血清转移诱导关节炎小鼠模型中,关节内注射编码IL-38的腺病毒相关病毒可通过抑制巨噬细胞和FLS产生炎症因子来减轻类风湿关节炎的严重程度 [ 34 ] ;反之,IL-38缺陷小鼠显示出严重的类风湿关节炎病变 [ 31 ] 。IL-36在体外也具有类似的炎症调节作用。IL-38可降低健康供者外周血单核细胞中热灭活白念珠菌诱导的IL-17和IL-22产生 [ 35 ] ;过表达IL-38单核巨噬细胞的条件培养基可以显著减少类风湿关节炎患者巨噬细胞和FLS中IL-6、TNF-α和IL-23的表达 [ 34 ] ;IL-38缺失可促进人原代巨噬细胞中IL-6和IL-8生成以及活化蛋白-1激活,进而诱导Th17细胞的扩增 [ 36 ] ,而Th17细胞在类风湿关节炎等多种自身免疫性疾病的发病机制中发挥着重要作用 [ 37 ] ,上述研究均提示IL-38在类风湿关节炎中发挥抗炎作用。IL-36β可促进滑膜成纤维细胞产生IL-6和IL-8 [ 38 ] ,提示IL-36在类风湿关节炎中发挥促炎作用。但Hao等 [ 39 ] 则发现,IL-36激动剂能抑制滑膜细胞的增殖、迁移和侵袭,而IL-38过表达质粒则具有相反的作用,可能与自噬调节相关。…”
Section: Il-36与类风湿关节炎unclassified
“…不同IL-36亚型在类风湿关节炎中的作用目前尚存在争议。在胶原性关节炎和K/BxN血清转移诱导关节炎小鼠模型中,关节内注射编码IL-38的腺病毒相关病毒可通过抑制巨噬细胞和FLS产生炎症因子来减轻类风湿关节炎的严重程度 [ 34 ] ;反之,IL-38缺陷小鼠显示出严重的类风湿关节炎病变 [ 31 ] 。IL-36在体外也具有类似的炎症调节作用。IL-38可降低健康供者外周血单核细胞中热灭活白念珠菌诱导的IL-17和IL-22产生 [ 35 ] ;过表达IL-38单核巨噬细胞的条件培养基可以显著减少类风湿关节炎患者巨噬细胞和FLS中IL-6、TNF-α和IL-23的表达 [ 34 ] ;IL-38缺失可促进人原代巨噬细胞中IL-6和IL-8生成以及活化蛋白-1激活,进而诱导Th17细胞的扩增 [ 36 ] ,而Th17细胞在类风湿关节炎等多种自身免疫性疾病的发病机制中发挥着重要作用 [ 37 ] ,上述研究均提示IL-38在类风湿关节炎中发挥抗炎作用。IL-36β可促进滑膜成纤维细胞产生IL-6和IL-8 [ 38 ] ,提示IL-36在类风湿关节炎中发挥促炎作用。但Hao等 [ 39 ] 则发现,IL-36激动剂能抑制滑膜细胞的增殖、迁移和侵袭,而IL-38过表达质粒则具有相反的作用,可能与自噬调节相关。…”
Section: Il-36与类风湿关节炎unclassified
“…It is noteworthy that there are few studies on the relationship between IL-36 cytokines and autophagy. A recent study revealed that IL-36 cytokines can improve rheumatoid arthritis symptoms by promoting synovial cell autophagy, thereby inhibiting synovial cell migration and invasion ( 77 ). In addition, IL-36β can enhance the autophagy of Tregs, and attenuate the immunosuppressive effect, improving the prognosis of patients with sepsis ( 47 ).…”
Section: Il-36 Cytokines and Autophagymentioning
confidence: 99%
“…PYCARD plays a fundamental role in the detection, modulation, and advancement of diverse inflammatory diseases [ 4 ]. IL-38 is a member of the IL-1 family that targets autophagy to regulate the proliferation, migration, and invasion of synovial cells in patients with RA [ 5 ]. Among inflammatory cytokines, IL-6 is the most prevalent in the synovium of patients with RA and has a strong predictive ability for the severity and progression of RA [ 6 ].…”
Section: Introductionmentioning
confidence: 99%